Peran RUBI Community Dalam Membangun Brand Engagement Avoskin di Media Sosial - Amalia, Hasna Nadia; Alfarizi, Muhammad Salma; Muntaha, Ahmad (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2025)
This study aims to analyze the role of RUBI Community in building Avoskin's brand engagement through social media. A qualitative research method with a case study approach was used, focusing on the activities of RUBI Community and the media relations strategies of PT AVO Innovation Technology. The results reveal that the community plays a vital role as brand advocates, content creators, and strategic communication partners. Through strategies such as content collaboration, education, exclusivity, and two-way communication, RUBI Community significantly enhances digital engagement, consumer loyalty, and positive word of mouth for the Avoskin brand. This study confirms that community-based approaches can be an effective solution for building sustainable brand-consumer relationships in the digital era.Keywords : Brand Engagement, Community, Social Media, Avoskin, Media Relations.